Anti-Neutrophil Cytoplasmic Antibody-Associated Ocular Manifestations in Japan: A Review of 18 Patients. (4th July 2021) - Miyanaga, Masaru; Takase, Hiroshi; Ohno-Matsui, Kyoko
ABSTARCT: Purpose : To investigate ocular manifestations in patients positive for serum anti-neutrophil cytoplasmic antibodies (ANCAs) in Japan. Methods : The clinical records of patients who had ocular manifestations and who were serum ANCA positive between 2011–2017 at Tokyo Medical and Dental University Hospital were retrospectively reviewed. Results : Eighteen patients were identified to be positive for serum ANCA and had ocular manifestations, including optic nerve involvement (50%), scleritis (27.8%), iritis (27.8%), retinal vasculitis (16.7%), oculomotor disorder (16.7%), and peripheral ulcerative keratitis (11.1%). Six patients had ANCA-associated vasculitis (AAV), including 5 patients with granulomatosis with polyangiitis and 1 patient with microscopic polyangiitis. Most patients with optic nerve involvement were myeloperoxidase-ANCA positive. Contrastingly, most patients with anterior segment involvement were proteinase-3-ANCA positive. Conclusion : Ocular manifestations were observed in some patients positive for serum ANCAs. Serum ANCA evaluation is useful for identifying the etiology of ocular inflammation and for diagnosing AAV, a life-threatening disease.